Mutation analysis of the CYP21A2 gene in congenital adrenal hyperplasia - Forouzanfar, K; Seifi, M; Hashemi-Gorji, F; Karimi, V; Estiar, M A; Karimoei, M; Sakhinia, E; Karimipour, M; Ghergherehchi, R (Cellular and Molecular Biology, 2015)
Congenital adrenal hyperplasia (CAH) is an inherited autosomal recessive enzymatic disorder involving the synthesis of adrenal corticosteroids. 21-Hydroxylase deficiency (21-OHD) is the most common form of the disease which is observed in more than 90% of patients with CAH. Early identification of mutations in the genes involved in this disease is critical. A marker of the disease, errors in the CYP21A2 gene, is thought to be part of the pathophysiology of CAH. Therefore, the identification of gene mutations would be very beneficial in the early detection of CAH. This research was a descriptive epidemiological study conducted on individuals elected by the inclusion criteria whom were referred to the Genetic Diagnosis Center of Tabriz during 2012 to 2013. After sampling and DNA extraction, PCR for the detection of mutations in the CYP21A2 gene was performed followed by sequencing. For data analysis, the results of sequencing were compared with the reference gene by blast, Gene Runner and MEGA-5 software. Obtained changes were compared with NCBI databases. The analysis of the sequencing determined the mutations located in Exons 6, 7, 8 and 10. The most frequent findings were Q318X (53%) and R356W (28%). Exon 6 cluster (7%), E431k (4%), V237E (2%), V281L (2%), E351K (2%), R426C (2%) were also frequent in our patients. The most frequent genotype was compound heterozygote, Q318X/R356W. Three rare mutations in our study were E431K, E351K and R426C. Observed mutation frequencies in this study were much higher than those reported in previous studies in Iranian populations. Thus, it seems that it is necessary to follow-up screening programs and use sequencing methods to better identify mutations in the development of the disease.